2020
DOI: 10.1038/s41598-020-68360-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and safety of IBI301 versus rituximab in patients with CD20+ B-cell lymphoma: a multicenter, randomized, double-blind, parallel-controlled study

Abstract: This multicenter, randomized, double-blind, parallel-controlled trial aimed to compare the pharmacokinetics (PK) of IBI301 with rituximab in patients with CD20-positive (CD20 + ) B-cell lymphoma, who achieved a complete response/unconfirmed complete response after standard treatments. Patients were randomized (1:1) to receive IBI301 or rituximab (375 mg/m 2 , IV). Patients who continuously benefitted from the trial after the PK phase underwent the extension phase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Twenty‐nine studies 13,15–21,25,26,28–30,32,34–37,39–47 reporting on RCTs were identified and included in the analysis, with 26 studies reporting efficacy outcomes (Table 2). Among all included studies, two reported on ABP 798, 17,18 two reported on BCD‐020, 28,41 eight reported on CT‐P10, 16,26,29–31,36,37,39,40 two reported on DRL‐Rituximab, 42,46 two studies reported on GP2013, 34,35 three reported on HLX01, 20,43,44 three reported on IBI301, 15,21,38 one reported on PF‐05280586, 19 two reported on RTXM83, 13,32,33 one reported on SAIT101, 25 and one reported on Zytux 45 (Table 2). All studies reported on treatment naïve patients, except for one study that reported on a single switch 16 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty‐nine studies 13,15–21,25,26,28–30,32,34–37,39–47 reporting on RCTs were identified and included in the analysis, with 26 studies reporting efficacy outcomes (Table 2). Among all included studies, two reported on ABP 798, 17,18 two reported on BCD‐020, 28,41 eight reported on CT‐P10, 16,26,29–31,36,37,39,40 two reported on DRL‐Rituximab, 42,46 two studies reported on GP2013, 34,35 three reported on HLX01, 20,43,44 three reported on IBI301, 15,21,38 one reported on PF‐05280586, 19 two reported on RTXM83, 13,32,33 one reported on SAIT101, 25 and one reported on Zytux 45 (Table 2). All studies reported on treatment naïve patients, except for one study that reported on a single switch 16 …”
Section: Resultsmentioning
confidence: 99%
“…Most patients were treated for FL or DLBCL, and all patients besides those in one study 16 reported on patients who were treatment naïve. Figure 4a — forest plot — summarises results from 10 studies 15,19–21,25,26,30,33,34,41 involving 3066 patients (biosimilar n = 1528, reference n = 1538). Comparable incidence of patients experiencing at least one TEAE with the biosimilar of rituximab was similar to the reference (OR 1.20, 95% CI: 0.98–1.49, p = 0.08).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations